2019
DOI: 10.1371/journal.pone.0223593
|View full text |Cite
|
Sign up to set email alerts
|

Deep architectures for long-term stock price prediction with a heuristic-based strategy for trading simulations

Abstract: Stock price prediction is a popular yet challenging task and deep learning provides the means to conduct the mining for the different patterns that trigger its dynamic movement. In this paper, the task is to predict the close price for 25 companies enlisted at the Bucharest Stock Exchange, from a novel data set introduced herein. Towards this scope, two traditional deep learning architectures are designed in comparison: a long short-memory network and a temporal convolutional neural model. Based on their predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…In addition, there is much evidence in the literature that hybrid LSTM methods outperform the other single DL methods [37]. In the application of the stock market, LSTM has been combined with different methods to develop a hybrid model.…”
Section: Lstmmentioning
confidence: 99%
“…In addition, there is much evidence in the literature that hybrid LSTM methods outperform the other single DL methods [37]. In the application of the stock market, LSTM has been combined with different methods to develop a hybrid model.…”
Section: Lstmmentioning
confidence: 99%
“…While LSTM have been constructed to possess a long-short term memory in order to handle temporal data [31], 1D CNN have recently also proved to be able to model time series within real-world applications either alone [32] or in combination with the former [33]. Therefore, the architecture used herein will be another combination of the two deep networks with 1D CNN being in charge of extracting the features and the LSTM of modeling the time dependencies.…”
Section: Deep Learning For the Classification Of Regrouped Saccadesmentioning
confidence: 99%
“…Feature engineering by CNN Figure 6 shows the accuracy of twenty (20) iterations of different randomly selected features by our CNN model. We observed that 21 features gave an accuracy of 82.52%, while 52 features recorded an accuracy of 81.06%, as shown in Fig.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…The proposed techniques perform favourably compared with traditional methods in terms of prediction accuracy. In the same way, Stoean et al [20] applied an LSTM based predictive model to predict the closing-price of twenty-five (25) firms enlisted on the Bucharest Stock Exchange, using historical stock price. Notwithstanding the achievement recorded by authors, they acknowledged in their conclusion that the fusion of multiple stock price indicators can improve prediction accuracy.…”
Section: Studies Based On Quantitative Datasetmentioning
confidence: 99%